2014
DOI: 10.1016/j.jtcvs.2013.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Late outcomes comparison of nonelderly patients with stented bioprosthetic and mechanical valves in the aortic position: A propensity-matched analysis

Abstract: In patients aged <65 years, despite an increase in the rate of reoperation with stented bioprosthetic valves and an increase in major bleeding events with mechanical valves, there is no significant difference in mortality at late follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 15 publications
1
65
0
Order By: Relevance
“…Some previous studies found that patients in this age group who received a mechanical valve had a better survival [8,9] whereas others did not find a survival difference between patients with a mechanical valve and a bioprosthesis [10,11].…”
Section: Editorialmentioning
confidence: 80%
“…Some previous studies found that patients in this age group who received a mechanical valve had a better survival [8,9] whereas others did not find a survival difference between patients with a mechanical valve and a bioprosthesis [10,11].…”
Section: Editorialmentioning
confidence: 80%
“…estimate severity because of the crescentic shape of the regurgitant orifice, and multiple parameters must be used to determine the severity of MR� 67,68 Even so, on the basis of the criteria used for determination of "severe" MR in RCTs of surgical intervention for secondary MR, 69- [76][77][78][79][80][81][82] 2014 recommendation remains current.…”
Section: Mitral Regurgitation 72 Stages Of Chronic Mrmentioning
confidence: 99%
“…T he use of bioprostheses has considerably increased in the past decade and has led to a substantial reduction of mechanical valve implantations [1]. This trend may be explained by an increasing number of studies reporting improved long-term durability of more recent tissue valve models [2]. Nevertheless, biologic aortic valve replacement (AVR) in patients younger than 60 years remains controversial, and the expected event rates for surgical and valve-related complications have not been clearly determined in this patient subset.…”
mentioning
confidence: 99%